N′-[(E)-3-Indol-3-ylmethylene]isonicotinohydrazide monohydrate - Xia, Liang-You (International Union of Crystallography, 2009)
Crystals of the title compound, C(15)H(12)N(4)O·H(2)O, were obtained from a condensation reaction of isonicotinylhydrazine and 3-indolylformaldehyde. The molecule assumes an E configuration, with the isonicotinoylhydrazine and indole units located on the opposite sites of the C=N double bond. In the molecular structure the pyridine ring is twisted with respect to the indole ring system, forming a dihedral angle of 44.72 (7)°. Extensive classical N—H⋯N, N—H⋯O, O—H⋯O and O—H⋯N hydrogen bonding and weak C—H⋯O interactions are present in the crystal structure.